The prevalence and transcriptional activity of the mucosal microbiota of ulcerative colitis patients. Issue 1 (December 2018) - Moen, Aina; Lindstrøm, Jonas; Tannæs, Tone; Vatn, Simen; Ricanek, Petr; Vatn, Morten; Jahnsen, Jørgen
Abstract Active microbes likely have larger impact on gut health status compared to inactive or dormant microbes. We investigate the composition of active and total mucosal microbiota of treatment-naïve ulcerative colitis (UC) patients to determine the microbial picture at the start-up phase of disease, using both a 16S rRNA transcript and gene amplicon sequencing. DNA and RNA were isolated from the same mucosal colonic biopsies. Our aim was to identify active microbial members of the microbiota in early stages of disease and reveal which members are present, but do not act as major players. We demonstrated differences in active and total microbiota of UC patients when comparing inflamed to non-inflamed tissue. Several taxa, among them theProteobacteria phyla and families therein, revealed lower transcriptional activity despite a high presence. TheBifidobacteriaceae family of theActinobacteria phylum showed lower abundance in the active microbiota, although no difference in presence was detected. The most abundant microbiota members of the inflamed tissue in UC patients were not the most active. Knowledge of active members of microbiota in UC patients could enhance our understanding of disease etiology. The active microbial community composition did not deviate from the total when comparing UC patients to non-IBD controls.